Modernization and Pesantren Based Community Development in Indonesia - Budiwiranto, Bambang (Universitas Islam Negeri Raden Intan Lampung, 2019)
Community development in the pesantren was initiated by Muslim activists who joined LP3ES and P3M in response to the excess of top-down Modernization (Developmentalism) of the New Order. Through these NGOs the activists strengthened the pesantren to become agents of community development at the grass root level.It is argued that despite the fact that LP3ES and P3M provided the pesantren with participatory methods absent from the top-down New Order development model, they share the Modernization paradigm with the New Order. This paradigm focuses more on service delivery and fails to offer an alternative for achieving macro social and political transformation.